Knowledge Management in Industry: A Brazilian Experience - de Vasconcelos, Maria Celeste Reis Lobo; Tavares Ferreira, Marta Araújo (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Technological innovation is one of the main sources of development and competitiveness. Innovation is an interactive process accomplished through the contribution of scientific, technical and economical agents, each providing different types of information and knowledge. So innovative companies must be specially competent on generating and managing knowledge. This paper presents the results of a survey on knowledge processes and practices...